The biogeochemistry of some heavy metals and metalloids in the Ob River Estuary - Kara Sea section. - Demina, Lyudmila L; Gordeev, Viacheslav V; Galkin, Sergey V; Kravchishina, Marina D; Aleksankina, S P (PANGAEA, 2010)
Biogeochemical behavior of a group of heavy metals and metalloids in water (including their dissolved and suspended particulate forms), bottom sediments, and zoobenthos was studied in the Ob River estuary (Obskaya Guba) - Kara Sea section on the basis of data obtained during Cruise 54 of R/V Akademik Mstislav Keldysh in September-October 2007. Changes in ratios of dissolved and particulate forms of Fe, Mn, Zn, Cu, Pb, Cd, and As were shown, as well as growth of adsorbed fractions of the elements in near-bottom suspended matter under mixing of riverine and marine waters. Features of chemical element accumulation in typical benthic organisms of the Obskaya Guba and the Kara Sea were revealed, and their concentrating factors were calculated based on specific conditions of the environment. It was shown that shells of bivalves possessing higher biomass compared to other groups of organisms in the Obskaya Guba play an important role in deposition of heavy metals. In the Obskaya Guba mollusks accumulate Cd and Pb at the background level, whereas Cu and Zn contents appear to be higher than the background level.
Chemical composition of waters, suspended matter, bottom sediments, and benthic organisms along a section from the Ob River estuary (Obskaya Guba) to the central Kara Sea
Keywords: Akademik Mstislav Keldysh; AMK54; AMK54-4983; AMK54-4990; AMK54-4993; AMK54-4994; AMK54-4995; AMK54-4996; AMK54-4999; AMK54-5000; AMK54-5001; AMK54-5002; AMK54-5003; AMK54-5004; Archive of Ocean Data; ARCOD; Kara Sea; MULT; Obskaya Guba